A DFT study of the adsorption of O2 and H2O on Al(111) surfaces. Issue 61 (13th June 2016) - Wei, Xin; Dong, Chaofang; Chen, Zhanghua; Xiao, Kui; Li, Xiaogang
Abstract : Using first-principles calculations that are based on density functional theory, the molecular and dissociative adsorptions of O2 and H2 O on a clean and O pre-adsorbed Al(111) surface were systematically investigated. Abstract : Using first-principles calculations that are based on density functional theory, the molecular and dissociative adsorptions of O2 and H2 O on a clean and O pre-adsorbed Al(111) surface were systematically investigated. The van der Waals dispersion correction is considered for the molecular adsorption of H2 O. We found that O2 dissociates into O atoms which can adsorb on fcc and hcp sites. The stability ranking for O atoms on the clean Al(111) surface is fcc > hcp. The energy barriers for the migration of a single O atom from a hcp to a fcc site on a clean and O pre-adsorbed Al(111) surface are 25.91 kJ mol −1 and 28.67 kJ mol −1, respectively, which means that the pre-adsorbed O atom inhibits the migration of O atoms on the surface. H2 O molecules cannot dissociate on both clean and O pre-adsorbed Al(111) surfaces spontaneously. The pre-adsorbed O atom can strengthen the adsorption of H2 O and promote its deformation. The dissociation adsorption of H2 O, that is, the co-adsorption of OH and H, is much stronger than the molecular H2 O adsorption. The energy barrier of H2 O dissociation is 137.58 kJ mol −1 on a clean Al(111) surface, however, it decreases to 38.18 kJ mol −1 with the aid of a pre-adsorbed O atom, suggesting that a pre-adsorbed O atom can promote the dehydrogenation reaction of H2 O.